P-056 Development of a Clinical Care Pathway to Identify and Treat Malnutrition in Patients with Inflammatory Bowel Disease. (February 2017) - Hwang, Caroline; Reddy, Swapna; Issokson, Kelly; Giguere-Rich, Catherine; Tinsley, Andrew; Bray, Harry; Lum, Donald; Aguilar, Humberto; Zisman, Timothy; Younes, Ziad; Nguyen, Anne; Crate, Damara; et al.
Abstract : Background: Patients with inflammatory bowel disease (IBD) patients are at increased risk for malnutrition due to multiple factors including chronic inflammation, malabsorption, and food restriction. Malnutrition has been associated with depressed immune function, longer hospitalizations, and increased perioperative complications, and has also been identified as a quality measure in IBD. We have previously demonstrated significant knowledge gaps among gastroenterologists on how to recognize and treat malnutrition. We therefore aimed to develop an evidence-based Nutrition Care Pathway (NCP) to identify and manage malnutrition in IBD. Methods: A steering committee made up of gastroenterologists with expertise in IBD, dietician, experts in care pathway development, and representatives from the Crohn's and Colitis Foundation of America (CCFA), drafted goals and a framework for an NCP specific to IBD. These were discussed and refined at a moderated, 2-day in-person workshop that included gastroenterologists, dieticians, patient representatives (AW1), informatics experts, and education and advocacy representatives of the CCFA. The steering committee then further refined the NCP, based on additional review of published literature, societal guidelines and care pathways for nutrition assessment in other chronic diseases. The screening component of the NCP was then tested at 7 university-based and community gastroenterology practices participating in CCFA's Qorus Program, a multicenter learning health system designed to improve quality of care in IBD. In addition to the self-administered screening tool, patients rated the ease of administration, and relevance of nutrition screening to their care. Results: The NCP includes 4 stages: (1) malnutrition screening (2) clinical assessment (3) treatment and (4) monitoring/follow-up. The NCP screening stage incorporates the validated Malnutrition Universal Screening Tool (MUST), which patients complete prior to a clinical visit. The MUST stratifies patients as low-, moderate- or high-risk for malnutrition. Low-risk patients are directed to re-screen annually, without proceeding on to further NCP stages. Moderate-risk patients undergo focused clinical assessment by providers and are observed for worsening nutritional status. High-risk patients undergo expanded clinical assessment and are provided gastrointestinal symptom-based treatment by providers, and are also referred to a dietician for nutritional education and enteral/parenteral support. The NCP also includes educational materials for both providers and patients, and guidance on appropriate laboratory testing at relevant stages. A total of 247 patients with IBD have completed the NCP screening component. Of these, 21% reported weight loss of ≥5% in the past 6 months, and 7% had a body mass index (BMI) of <18.5. Overall, 20% of screened patients were found to be at high-risk for malnutrition, 16% at moderate-risk and 64% low-risk. Eighty-six percent of patients responded that it was either very easy or easy to complete the MUST. Conclusions: We have developed an evidence-based Nutrition Care Pathway for IBD using multidisciplinary expert and patient input. Screening for malnutrition using the NCP is feasible across a variety of ambulatory gastroenterology practice settings and our early experience demonstrates that over one-third of patients with IBD are at risk for malnutrition. Testing of the assessment, treatment, and follow-up stages is warranted in order to evaluate the impact of the NCP on patient outcomes.